Technological Innovation is Needed to Accelerate Stunting Reduction in Indonesia - Herman Yuliansyah; Surahma Asti Mulasari; Sulistyawati Sulistyawati (Epidemiology and Society Health Review (ESHR), 2022)
The Indonesian government has implemented programs to reduce stunting by targeting several groups, including: pregnant and maternity mothers, toddlers, school-age children, adolescents, and young adults. The actions include interventions and efforts to increase knowledge among the related subject – mostly among women. These efforts must still have been carried out until recently. However, along with the development of the digital era, stunting prevention needs to involve technology as an innovation to predict the possibility of a toddler becoming stunted in the future when their intake is insufficient.